2020
DOI: 10.1037/apl0000450
|View full text |Cite
|
Sign up to set email alerts
|

Putting leaders in a bad mood: The affective costs of helping followers with personal problems.

Abstract: Although leaders spend considerable time helping followers with personal problems, little research has investigated how such helping acts may impact leaders themselves. Drawing from affective events theory and the helping literature, we examine how responding to followers' help requests with personal problems influences leaders' own affect. As expected, we found that helping followers with personal problems was associated with an increase in leaders' negative affect. The strength of the association between per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 111 publications
(209 reference statements)
3
64
0
1
Order By: Relevance
“…They were removed from the final sample because at least three observations per person are recommended to appropriately model within-individual variations and to obtain a representative experience of the employee (Beal et al, 2013). Further, this approach is aligned with common practices in similar daily diary designs (e.g., Gabriel et al, 2018;Lanaj & Jennings, 2020). Thus, the final sample consisted of 189 employees (Level 2) who provided 1,612 day-level observations (Level 1), rendering a compliance rate of 85% (i.e., 1,612 / [189 × 10]).…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…They were removed from the final sample because at least three observations per person are recommended to appropriately model within-individual variations and to obtain a representative experience of the employee (Beal et al, 2013). Further, this approach is aligned with common practices in similar daily diary designs (e.g., Gabriel et al, 2018;Lanaj & Jennings, 2020). Thus, the final sample consisted of 189 employees (Level 2) who provided 1,612 day-level observations (Level 1), rendering a compliance rate of 85% (i.e., 1,612 / [189 × 10]).…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…Both explicit and implicit emotional contagion mechanisms suggest that the length and frequency of affective interactions among individuals can influence the extent to which they share emotion [ 25 ]. More specifically, these mechanisms suggest that the longer and the more frequently team members participate in affective interactions or observe each other’s emotional expression, the more likely that they will feel similar and thus result in shared emotion or emotional convergence.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…However, helping followers can bring negative implications on leaders' well‐being as interpersonal helping could generate costs for helpers (Bolino & Grant, 2016 ). For example, Lanaj and Jennings ( 2020 ) showed that leaders responding to followers' personal requests can increase leaders' negative affect. In light of the above, we seek to understand how unclear demands from followers during the COVID‐19 can affect leaders' well‐being and use the defeat‐entrapment theory (Gilbert, 2006 ; Taylor et al, 2011 ) to guide our theorising and empirical examination.…”
Section: Introductionmentioning
confidence: 99%
“…exhibition of positive leadership, answering followers' personal requests) consume leaders' personal sources, thus resulting in lower levels of well‐being (e.g. Lanaj & Jennings, 2020 ; Lin et al, 2019 ). We go beyond a resource perspective and focus on leaders' perception by showing that followers' unclear demands can cause leaders to cognitively view the situation as aversive and feel trapped in their responsibilities.…”
Section: Introductionmentioning
confidence: 99%